Sacrificial bumpers with high-impedance ceramic coating for orbital debris shielding: A preliminary experimental and numerical study. (September 2018) - Cherniaev, Aleksandr; Telichev, Igor
Highlights: Potential of ceramo-aluminum laminates as Whipple shield bumpers was studied. Laminated bumpers induce higher tensile stresses in hypervelocity projectiles. Laminated bumpers provide better hypervelocity projectile fragmentation. Abstract: This study investigates the potential of layered ceramo-aluminum sacrificial bumpers as external elements for spacecraft orbital debris shielding. The bumpers are tailored based on the principle of matching shock impedance of ceramic and metallic layers. They consist of aluminum substrate coated from both sides with silicon carbide. The investigation of the bumpers' performance included both hydrocode modeling and physical hypervelocity impact (HVI) experiments. Obtained results indicate that coated ceramo-aluminum bumpers provide better fragmentation of hypervelocity projectiles and can be considered as a substitute for all-aluminum bumpers in the design of orbital debris shielding.